Analisis Faktor yang Mempengaruhi Resiliensi Akademik Mahasiswa saat Penyelesaian Skripsi - Ade Laili Jum'ati Surya; Armiati Armiati (Jurnal Ecogen, 2023)
This research aims to analyze the factors that influence students' academic resilience when completing their thesis at the Faculty of Economics and Business, Padang State University. This type of research is quantitative and descriptive. The population of this study included students form the 2016-2018 session of the Faculty of Economic and Bussines Padang State University, with a total of 473 students who completed their thesis. The data collection technique uses a questionnaire using a sampling technique, namely proportional random sampling technique. The sample of this study included 83 students. The data obtained was processed using descriptive analysis and confirmatory factor analysis. The results of the research show that there are 5 factors that influence the academic resilience of students at the Faculty of Economics and Business, Padang State University, namely the self-regulation factor, the social support factor, the academic procrastination factor, the optimism factor and the spirituality factor. The dominant factor that influences students' academic resilience when completing their thesis is the self-regulation factor.